2019
DOI: 10.1021/acsomega.9b01027
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of MoO3 Thin-Film Properties Due to Annealing in Situ Monitored by Hard X-ray Photoemission

Abstract: The chemical and electronic structure of MoO 3 thin films is monitored by synchrotron-based hard X-ray photoelectron spectroscopy while annealing from room temperature to 310 °C. Color-coded 2D intensity maps of the Mo 3d and O 1s and valence band maximum (VBM) spectra show the evolution of the annealing-induced changes. Broadening of the Mo 3d and O 1s spectra indicate the reduction of MoO 3 . At moderate temperatures (120–200 °C), we find spectral evidence for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…These peaks indicate negligible oxygen vacancies in the synthesized α-MoO 3 thin films. [23] These investigations substantiate the fact that the chemical and structural properties of our fabricated rectangular-shaped α-MoO 3 thin films using thermal physical deposition technique are as expected.…”
Section: Resultssupporting
confidence: 85%
“…These peaks indicate negligible oxygen vacancies in the synthesized α-MoO 3 thin films. [23] These investigations substantiate the fact that the chemical and structural properties of our fabricated rectangular-shaped α-MoO 3 thin films using thermal physical deposition technique are as expected.…”
Section: Resultssupporting
confidence: 85%
“…Lee et al reported that MoO x HTL-based OSCs are more stable at a high operating temperature near 300-420 K than PEDOT:PSS [90]. Therefore, there is much research in strategies to optimize the solution-processing methods and the film properties of MoO 3 [91][92][93]. Bortoti et al obtained the orthorhombic phase of MoO 3 (α-MoO 3 ) by refluxing MoS 2 in HNO 3 and H 2 SO 4 as the oxidant media, followed by heating at 120 • C for 10 min to evaporate the solvent [94].…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…Thus, it cannot be excluded that the extended exposure of the Cu x Ni 1− x O y library to X-rays (in total: several 100 hours) altered some of its properties. However, no reduction or ‘metallization’, as reported for other metal oxides like WO 3 14 and MoO 3 , 15 was observed during the measurements. In contrast, the Cu 2p data of measurement spots 7 and 163 (shown in S.I.…”
Section: Methodsmentioning
confidence: 57%